Egypt and Moab - Worschech, Udo 1942- (1997)
The earliest references to the peoples of Moab appear in two inscriptions from the reign of Ramesses II. While Egyptian sources offer nothing regarding Moab during the Iron Age, fortunately, other sources, such as the Bālū˓ Stele and the Mesha Inscription, step in. On the whole, the evidence suggests that Moab was a larger political factor than historians have realized.